2019
DOI: 10.1111/jcmm.14921
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of canonical and non‐canonical TGF‐β signalling on mixed contractile‐synthetic smooth muscle cell phenotype in human Marfan syndrome aortic root aneurysms

Abstract: Aortic root aneurysm formation is a cardinal feature of Marfan syndrome (MFS) and likely TGF-β driven via Smad (canonical) and ERK (non-canonical) signalling. The current study assesses human MFS vascular smooth muscle cell (SMC) phenotype, focusing on individual contributions by Smad and ERK, with Notch3 signalling identified as a novel compensatory mechanism against TGF-β-driven pathology. Although significant ERK activation and mixed contractile gene expression patterns were observed by traditional analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 51 publications
3
35
1
Order By: Relevance
“…Applying an iTRAQ proteomic strategy, iPSC derived SMCs from MFS patients are utilized to model and investigate human disease mechanisms and discover novel biological pathways that participate in early ECM degeneration. SMC modulation from contractile to the dedifferentiated, synthetic phenotype is known to contribute to aortic aneurysm development 3,35,40 . We recently reported on the "mixed SMC phenotype" in human MFS aortic tissue and primary vascular SMC lines, which overexpressed both contractile and synthetic genes 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying an iTRAQ proteomic strategy, iPSC derived SMCs from MFS patients are utilized to model and investigate human disease mechanisms and discover novel biological pathways that participate in early ECM degeneration. SMC modulation from contractile to the dedifferentiated, synthetic phenotype is known to contribute to aortic aneurysm development 3,35,40 . We recently reported on the "mixed SMC phenotype" in human MFS aortic tissue and primary vascular SMC lines, which overexpressed both contractile and synthetic genes 35 .…”
Section: Discussionmentioning
confidence: 99%
“…SMC modulation from contractile to the dedifferentiated, synthetic phenotype is known to contribute to aortic aneurysm development 3,35,40 . We recently reported on the "mixed SMC phenotype" in human MFS aortic tissue and primary vascular SMC lines, which overexpressed both contractile and synthetic genes 35 . Similarly, Crosas-Molist et al 36 observed an overexpression of both contractile markers and collagen I in human MFS specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF‐β signalling was demonstrated to regulate MSCs’ phenotypic switch and prevent the development of TAD (Milewicz & Ramirez, 2019; Pedroza et al., 2020). Here, we sought to study the molecular mechanism of IGFBP3 in TAD and examine whether the TGF‐β–Smad2 pathway was involved in IGFBP3‐mediated mAoSMCs’ phenotype transformation.…”
Section: Resultsmentioning
confidence: 99%
“…The human pericardium is composed of fibroblasts and collagen. If the majority of the media is resected as a dissection flap and replaced with pericardium, the elastic aortic root becomes a very stiff aortic root, which is likely more susceptible to aortic root aneurysm as seen in patients with Marfan disease, 8,9 who have significantly more collagen in the aortic root compared to normal people. Technically, it is much more complex to replace all the dissection flaps in 3 aortic sinuses 1 and have more needle holes causing bleeding than simply to obliterate the false lumen by closing the dissection at the sinotubular junction.…”
Section: Reply: Respect Mother Nature-aortic Root Repair In Acute Typmentioning
confidence: 99%